The Added Value of Specialty Ground Coffee at Gunung Mas Jaya Agroindustry, Situbondo Regency - Indriyani; Gema Iftitah Anugerah Yekti; Yasmini Suryaningsih (Jurnal Ilmu Pertanian Indonesia, 2025)
Coffee is a key commodity in Indonesia's plantation subsector, offering prospects both locally and internationally. The rise in Indonesian coffee production over the last decade has coincided with shifts in people's coffee consumption habits. The expansion of coffee shops and cafés in Indonesia has had a considerable impact on coffee demand, especially for processed coffee products. This creates an opportunity for coffee producers and the coffee agroindustry to supply high-value-added coffee goods, such as specialty coffee powder created by Gunung Mas Jaya Agroindustry. The purpose of this study was to assess the value added of specialty coffee powder at Gunung Mas Jaya. The descriptive-quantitative technique employed both primary and secondary data sources. Respondents were chosen using purposive sampling at Gunung Mas Jaya Agroindustry. The Hayami approach was used in data analysis to calculate value-added. The analysis results suggest that the value added of specialty ground coffee is 87.56%, placing it in the top category (VA > 50%). The profit rate for specialty ground coffee is 98.08%, showing that it has a lot of room for growth due to its high profitability. Keywords: agroindustry, Hayami Method, specialty ground coffee, value added